Reducing Traffic Congestion in Beirut : An Empirical Analysis of Selected Policy Options - Anas, Alex; De Sarkar, Sayan; Abou Zeid, Maya; Timilsina, Govinda; Nakat, Ziad (World Bank, Washington, DC, 2017)
Beirut, the capital city of Lebanon, faces huge traffic congestion, the cost of which is estimated to be more than 2 percent of the city's gross regional product. Effective policies are needed, based on weighing their overall economic cost and benefit to society. This study developed an empirical model based on microeconomic theory, accounting for production and consumption behavior related to transportation in the Greater Beirut Area, to simulate various policy combinations. A key finding of the study is that individual supply-side policies, such as the expansion of roads or introduction of a bus rapid transit system, are quite effective at reducing traffic congestion while increasing economic output and welfare. They also account for most of the benefits from implementing policy packages with supply- and demand-side measures. The introduction of bus rapid transit with expansion of the road system to feed the bus rapid transit system reduces congestion by about 16 percent and congestion costs by more than 50 percent. This would increase Beirut's gross regional product by roughly 2 percent, and the average social welfare of the residents of Beirut by 4 percent. In contrast, demand-side instruments, implemented alone, lower gross regional product and welfare with limited effects on congestion.